2006
DOI: 10.1007/s10562-006-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen activated by the active vanadium species for the selective oxidation of benzene to phenol

Abstract: The activation of oxygen is a key step for the selective oxidation of benzene to phenol and the reason is discussed. The active oxygen species is produced from molecular oxygen in a so-called ''reductive activation'' process. The vanadium oxide supported on alumina was pre-reduced by hydrogen or ascorbic acid to lower valence vanadium species acting as reduction source and the activity is investigated in the reaction. It is found that the V 4+ valence vanadium (VO 2+ ) is effective for the reaction from the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The V 4? species in PMoV could activate dioxygen as active species for accelerating the oxidation process [33]. For the current newly prepared L-Mn-PMoV catalyst, it is suggested that L-Mn acts as a modifier to create an electron donor-accepter system via the coordinate bond between the Mn center and the terminal oxygen atom of PMoV [23].…”
Section: Catalytic Performancementioning
confidence: 97%
“…The V 4? species in PMoV could activate dioxygen as active species for accelerating the oxidation process [33]. For the current newly prepared L-Mn-PMoV catalyst, it is suggested that L-Mn acts as a modifier to create an electron donor-accepter system via the coordinate bond between the Mn center and the terminal oxygen atom of PMoV [23].…”
Section: Catalytic Performancementioning
confidence: 97%
“…Due to the high bond energy of the C-H bond (472.2 kJ mol -1 ) [37], benzene was difficult to be oxidatively hydroxylized to phenol. Many efforts have been made for the process, but the yield for phenol was not satisfactory so far [38,39]. In many reported catalysts systems, such as LaOx/HZSM-5 [40], PMoV 1 -b-CyDs [41], Cu/ZnO [42], etc., some co-reducing agent, such as ascorbic acid, was necessary to achieve the conversion of phenol.…”
Section: Resultsmentioning
confidence: 99%
“…Much effort has been made to produce phenol by hydroxylation of benzene with molecular oxygen under mild conditions. [11][12][13][14][15][16][17] However, the mechanism and the factors affecting the selectivity are still not clear for the hydroxylation of benzene to phenol in the liquid phase. With H 2 O 2 as the oxidant agent, C]O and the armchair conguration defects in the carbon catalyst were reported to have a positive effect on the yield of phenol.…”
Section: Introductionmentioning
confidence: 99%